Effect of intra-membrane C60 fullerenes on the modulus of elasticity and the mechanical resistance of gel and fluid lipid bilayers. Issue 40 (30th September 2015) - Zhou, Jihan; Liang, Dehai; Contera, Sonia
Abstract : AFM imaging and nanoindentation complemented by FTIR and light scattering revealed the effect of intramembrane fullerene C60 on fluid and gel phase lipid bilayers. Abstract : Penetration and partition of C60 to the lipid bilayer core are both relevant to C60 toxicity, and useful to realise C60 biomedical potential. A key aspect is the effect of C60 on bilayer mechanical properties. Here, we present an experimental study on the mechanical effect of the incorporation of C60 into the hydrophobic core of fluid and gel phase zwitterionic phosphatidylcholine (PC) lipid bilayers. We demonstrate its incorporation inside the hydrophobic lipid core and the effect on the packing of the lipids and the vesicle size using a combination of infrared (IR) spectroscopy, atomic force microscopy (AFM) and laser light scattering. Using AFM we measured the Young's modulus of elasticity ( E ) of 1, 2-dipalmitoyl- sn-glycero -3-phosphocholine (DPPC), 1, 2-dimyristoyl- sn-glycero -3-phosphocholine (DMPC) and 1, 2-distearoyl- sn-glycero -3-phosphocholine (DSPC) in the absence (presence) of intra-membranous C60 at 24.5 °C. E of fluid phase supported bilayers is not altered by C60, but E increases with incorporation of C60 in gel phase bilayers. The increase is higher for longer hydrocarbon chains: 1.6 times for DPPC and 2 times for DSPC. However the mechanical resistance of gel phase bilayers of curved bilayered structures decreases with the incorporation of C60 . Our combined results indicate that C60 causes a decrease in gel phase lipid mobility, i.e. an increase in membrane viscosity.